Evaluation of skeletal metastatic pattern by 99m Tc- Methylene diphosphonate in prostatic carcinoma patients (Bangladesh Journal of Nuclear Medicine, 2016)
Objective: The objective of this study was to find out the pattern of skeletal metastasis in-patient with prostatic carcinoma by using 99mTechnetium-Methylene diphosphonate (99mTc MDP).Methods: This retrospective study was carried out at the National Institute of Nuclear Medicine and Allied Sciences (NINMAS) from January 2014 to December 2014. The study included 65 histologically proven prostatic carcinoma patients. They were divided into three groups according to their age. Whole body bone scintigraphy was performed with 99mTc MDP and was interpreted by expert nuclear medicine physicians as negative or positive for skeletal metastases.Results: Bone scan was done on 65 prostate cancer patients. They were divided into three groups according to their age. In this series, the lowest age of patients were 50 years and highest 85 years with a mean ± SD was 65.80 ± 10.11 years. Group A comprised of 14 subjects age ranged 50 to 59 years. Out of them 8 (57%) were positive for skeletal metastasis. Group B comprised of 25 subjects and age range from 60 to 69 years. Out of them 18(72%) were positive for skeletal metastasis. Third group C comprised of 26 subjects and age ranged from 70-80+ years of age. Out of 26 subjects 22(84%) were positive for skeletal metastasis. The most common site involved was dorsal vertebrae in which 60% secondaries were isolated. Sacroiliac joint 39% and ribs 33% were the second and third most common affected areas respectively. Other involved sites were skull, sacrum, lumbar vertebrae, ileum, mandible, femur, sternum, cervical vertebrae, iliac crest, scapula, hip joint, tibia and pelvis.Conclusion: This retrospective study focused on the pattern of skeletal metastasis in various bony sites due to prostate carcinoma, which might be helpful for the oncologist and clinician in further treatment planning.Bangladesh J. Nuclear Med. 17(2): 130-133, July 2014